THE EXPRESSION OF HIDDEN INFORMATION THROUGH PROVERBS - Nazarov Qobilbek (Journals Park Publishing, 2025)
In this article, proverbs used in various types of texts in the Uzbek language are pragmatically analyzed. During the analysis, the contextual explicit and implicit meanings of proverbs within texts are examined, and both hidden and open expressions of the information conveyed through proverbs are identified.
Keywords: Presupposition, hidden information, explicit information, communicative purpose, implication.